Digital Justice: Accessibility Factors of Smartphone Apps for Criminal Legal System-Involved People - Morgan, Gemma (The prison journal, 2025)
Digital technologies, particularly apps, are increasingly used to support criminal legal system-involved people (CLSIP). However, research on CLSIP's access to smartphones, data, and digital skills is limited. Our mixed methodology study, involving 41 CLSIP in Wales, UK, explored smartphone and app usage via observations and a survey. Findings reveal multifaceted barriers ranging from affordability, digital competency, literacy, and trust issues. The article advocates for training to enhance digital skills, subsidized access to smartphones/data, and the co-production of apps to improve accessibility for CLSIP. It outlines directions for future research, policy, and practice to support the digital inclusion of CLSIP.